A Case for Clarity: Defining Food System Drivers, Outcomes, and Feedbacks - Hasnain, Saher; Hill, Genia (The International Journal of Sociology of Agriculture and Food, 2025)
Food systems frameworks are useful analytical tools for understanding the functioning of a complex set of activities, stakeholders, and system outcomes, and for developing interventions for more desirable futures. Despite the rapid proliferation of food systems framings in recent decades, the field remains under-theorised with inconsistent andambiguous terminology for core concepts like ’drivers’, ’outcomes’, and ’feedbacks’. This lack of clarity hinders effective communication, research, and intervention design. This paper argues that clarifying these terms is essential for advancing food systems understanding and informing transformative action. We begin by critically examining how these terms are currently used in the food systems literature, highlighting inconsistencies and potential implications. Drawing upon geography literature, which usefully examines spatial dynamics, scale, and human-environment interactions, we then explore how analogous concepts are employed, seeking potential cross-disciplinary learning and enrichment. Geographical perspectives, with their emphasis on spatial dynamics, scale, and human-environment interactions, offer valuable insights for refining our understanding of food system processes. Drawing on this interdisciplinary exploration, we propose that researchers more clearly indicate how the key concepts of ’drivers’, ’outcomes’, and ’feedbacks’ within food systems analyses are being used and offer a distillation of their relationships with each other as key system elements. This will promote more rigorous and consistent approaches to studying food system dynamics, facilitating more effective research, policy development, and practical interventions. Ultimately, this paper underscores the importance of terminological clarity and interdisciplinary collaboration for addressing the complex challenges facing food systems and achieving a more just and sustainable food future.